Surveillance of avian influenza in South Africa: A look at a zoological monitoring program and sampling of wild birds - Gaugh, Emily (My University, 2009)
Through this masters' field experience, I have gained exposure to many different aspects of disease surveillance, especially as it relates to avian influenza in South Africa. This report will consider three main opportunities that occurred over a ten week period. First, disease surveillance and monitoring at the National Zoological Gardens of South Africa (NZG) where I helped sample resident birds as well as some donated specimens in order to gain a significant amount of information on the prevalence of avian influenza at the zoo. Secondly, wild bird capturing and sampling to gain information on disease migration and ecology of South African wild birds. Third, proper diagnostic techniques used at the Oderstepoort Veterinary Institute laboratory for testing of avian influenza. While avian influenza is not an immediate risk in the country of South Africa, a lot can still take place in the form of surveillance and monitoring. This was a productive experience that allowed me to learn the basics of disease control, biological pathways of disease, viral diagnostics, and field sampling. Along with this opportunity, the NZG has begun an annual avian influenza monitoring program that will continue sampling birds in the future and the Global Avian Influenza Network for Surveillance (GAINS) program was able to get information on more birds in the Strandfontein area.
Keywords: Avian influenza; Wild birds; GAINS; Disease surveillance; Public health; National Zoological Gardens South Africa; Biology, Veterinary Science (0778)